The Influence Of Sales Promotions, Price, And Service Quality On Deliwafa Sidoarjo Consumer Satisfaction - Firda Kartika Sari; Satrio Sudarso; Mas Oetarjo (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The fashion industry is growing along with increasing consumer demand for quality products at affordable prices. This study aims to analyze the effect of sales promotion, price, and service quality on consumer satisfaction at Deliwafa Sidoarjo. The method used is a quantitative approach with multiple linear regression analysis technique. Data were collected through questionnaires distributed to 100 respondents who are Deliwafa customers. The results showed that sales promotion, price, and service quality partially and simultaneously have a significant effect on consumer satisfaction. Service quality is the variable that has the most dominant influence in increasing consumer satisfaction. Therefore, Deliwafa needs to improve its promotional strategy to be more creative, maintain competitive prices, and improve service quality in order to maintain customer loyalty and increase business competitiveness.